From above or from below? That is the question. Comparison of the supraorbital approach with the endonasal approach. A cadaveric study. (3rd September 2018) - Peraio, Simone; Chumas, Paul; Nix, Paul; Phillips, Nick; Tyagi, Atul
Abstract: Background: Nowadays the endoscopic endonasal approach is increasingly being used to remove craniopharyngiomas, tuberculum sellae meningiomas and other presellar and parasellar lesions and its value in anterior skull base surgery is undisputed. Herein, we assess the relative advantages, disadvantages and feasibility of the keyhole eyebrow approach and the endonasal endoscopic approach in four cadaveric heads for the removal of presellar and parasellar lesions. Methods: We used four cadaveric heads for 12 surgical dissections. The specimens were embalmed with two different techniques. Two bilateral supraorbital endoscopic assisted approaches and one transnasal expanded endonasal approach were performed for each head. We evaluated the feasibility, maneuverability and safety of each approach. We measured the operating room obtained with each approach and the distance from the main structures we reached. Results: The technical feasibility of the endoscopic endonasal transphenoidal approach and the supraorbital eyebrow approach was reproduced in all four cadaveric heads. The transnasal approach gave us a good operating field medial to the two optic nerves and the two carotid arteries anteriorly until the frontal sinus and, posteriorly, the basilar artery, the emergence of the superior cerebellar arteries and posterior cerebral arteries. After performing the supraorbital approach, we viewed a wider field of the anterior skull base and we were able to reach the ipsilateral carotid artery, the optico-carotid recess, the pituitary stalk, the lamina terminalis until the contra lateral optic nerve and carotid artery, keeping a wider angle of maneuverability. Conclusions: Although the endoscopic transnasal approach has developed in leaps and bounds in the last decade, other transcranial approaches maintain their value. The supraorbital endoscopic approach is a minimally invasive approach and seems to be optimal for those lesions wider than 2 cm in the lateral extension and for all the paramedian lesions.